(untitled) (Raparin Journal of Humanities (RJH), 2020)
This paper focuses on the impacts of technological changes in the newsroom practices, taking both Actor-Network Theory (henceforth ANT) developed by Latour, 1992; Callon, 1992 and Law, 1992), as well as the Community of Practice (henceforth COP) developed by Wenger, 1998 and Lave, 1991) in newsroom practices and news-making processes inside the newsroom of (KNN) a Kurdish news channel. The paper argues that both models provide a strong basis of understanding the situation of news practice and constructing a better environment of learning, shared projects, problem solving, focal actor roles, and translation processes. The paper explores how the ANT and COP models work together to provide in-depth understanding for media researchers in their study of newsroom technology. Through this paper the researcher will provide in-depth understanding surrounding the key concepts and principles of each model and employ these to analyses news practice and contemporary newsroom culture. Through the use of ANT and COP this paper seeks to understand the role of new technology tools, human and non-human actors in shaping journalists’ behavior in the newsroom. The date collection process based on the secondary data includes the in-depth interviews with news making crews in the newsroom and non-participate observation of the situation of automation system newsroom applied by KNN.